Effects of Celmanax supplementation to prepartum dairy cows on colostrum quality and the subsequent growth and health of their calves - Campos Granados, Carlos Mario (2014)
The objective of this study was to assess the effects of supplementing prepartum dairy cows with a product derived from yeast culture and enzymatically hydrolyzed yeast cell wall (Celmanax (CEL), Vi-COR, Mason City, IA) on colostrum quality and the subsequent health and performance of their calves. Thirty prepartum multiparous Jersey cows were blocked by parity, body condition 21 days before expected calving date and productive and reproductive performance, and randomly assigned within block to 1 of 2 treatments (n=15) from 21 days before expected calving date until calving. Rations were top-dressed with CEL at the rate of 0 or 40 g/d throughout the experiment. Calves were fed 3 L of colostrum from their dam within two hours of birth and then 4 L of whole milk daily through week 8. Total Ig in colostrum from each cow was evaluated at 25oC from the first milking with a Colostrometer™ and a sample was taken for determination of IgG by ELISA. Approximately 48 hours after birth, a blood sample was drawn by venipuncture from each calf for the determination of serum protein by refractometer and IgG by ELISA. Daily feed intake, weekly weight and hip height and the incidence of pneumonia and scours were recorded. Data were analyzed using mixed models with repeated measures over time. Total Ig in colostrum was significantly increased by CEL treatment (P<0.05; 90.06±23.74 vs. 105.94±17.59 mg/mL for 0 and 40 g/d, respectively) but there was no effect on colostrum yield or IgG content (P>0.05). There was no effect of treatment on birth weight, serum protein or serum IgG (P>0.05). Average daily gain (382.86±61.20 vs. 410.94±51.22 g/day for 0 and 40 g/day, respectively), hip height increase (1.45±0.33 vs. 1.70±0.31 cm/week for 0 and 40 g/d, respectively) and feed consumption (446.67±9.92 vs. 439.01±6.12 g/day for 0 and 40 g/d, respectively) were not affected by treatment (P>0.05). Odds ratios were calculated and the odds of a calf presenting with scours or pneumonia were 3.5 and 5.0, respectively, times more likely in the calves whose dams did not consume CEL prepartum. CEL supplementation prepartum improved colostrum quality and calf health.